Pengembangan IoT Playground untuk Peningkatan Pemahaman Konsep IoT pada Siswa Sekolah Dasar - Nurhadiansyah; Qudwatullathifah, Ratri Nuryani; Alfairisi, Mohammad Ibnu Ayip; Roainah, Falamah (Institut Teknologi Garut, 2025)
This study aims to develop an IoT Playground as an interactive demonstration system that supports technology-based foundational learning. The product developed, called KERETA (Kendali Energi Rumah Edukatif Terpadu Otomatis), is a smart-lamp prototype in the shape of a train head designed to increase elementary students’ interest in learning through contextual and exploratory approaches. The system utilizes a NodeMCU ESP8266 microcontroller integrated with the Blynk application to wirelessly control and monitor the device via the internet. The research employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) with a limited trial involving 44 elementary school students. Practicality test results showed positive responses from teachers (89.5 percent) and students (86.7 percent), indicating that the tool is easy to use and effective in enhancing students’ understanding of basic Internet of Things (IoT) concepts. Effectiveness analysis using a paired t-test revealed a significant increase in students’ knowledge and learning participation after using the tool. The product functions not only as an interactive learning medium but also as a means of fostering digital literacy among young children. The IoT Playground KERETA innovation is expected to serve as a foundation for supporting the Indonesia Emas 2045 vision through the integration of technology in primary education.